Bioactive compounds of beetroot and utilization in food processing industry: A critical review. (30th January 2019) - Chhikara, Navnidhi; Kushwaha, Komal; Sharma, Paras; Gat, Yogesh; Panghal, Anil
Highlights: Beetroot is a root vegetable with carotenoids, phenolics, flavonoids and vitamins. Water soluble pigments betalains like betacyanins and betaxanthins. Beetroot is a gold mine of antioxidants due to the presence of betalains. Bioactive compounds associated with diverse health benefits. Beetroot, a boon to the food industry, used as food colorant or food additive. Abstract: Beetroot is recognized as health promoting food due to presence of essential components such as vitamins, minerals, phenolics, carotenoids, nitrate, ascorbic acids and betalains that promote health. Betalains occur in two forms i.e. betacyanin (red-violet pigment) and betaxanthin (yellow-orange pigment) and are recognizable commercially as a food dye due to non-precarious, non-toxic, non-carcinogenic and non-poisonous nature. Beetroot is premeditated as a boon for the food industry and used as food colorant or additive in food products such as ice-cream, yogurts and other products. The beetroot extract is used to improve the redness in tomato pastes, soups, sauces, desserts, jams, jellies, sweets and breakfast cereals. Overall objective of this review is to provide a brief knowledge about the valuable phytochemicals and bioactive compounds present in beetroot and their association with health benefits, beetroot processing for food application and their effect on beetroot pigment.